Decision Support System for Determining the Best PAUD Teacher Using the MOORA Method - Ade Yusupa; Jontinus Manullang; Nasib Marbun; Suranta Bill Fatric Ginting (SAGA: Journal of Technology and Information System, 2023)
Giving rewards is one of the efforts made to increase the motivation of PAUD Teacher to build better performance in educating early childhood. In this study we used a decision support system using the MOORA method to determine the best PAUD Teacher who is entitled to rewards without any jealousy from other unselected candidates. On the results of this study, the alternative Alexander Putra was chosen as the best PAUD teacher with a score of 0.4547 which is the highest score compared to other participants.